Customer Satisfaction towards Photocopiers W.r.t Xerox in Hyderabad - Prageetha Raju, G. (Indian Journal of Marketing, 2008)
The objective of the study is to identify the level of customer satisfaction towards Xerox Copiers and Corporation. The sample size is 200 respondents and the type of sampling is Convenience Sampling. Xerox Modi Corporation Limited owns a strong market share and brand image. Of the total consumers studied, 50% preferred Xerox, while 17% chose Canon, and 7% chose Ricoh. The rest preferred other brands like Godrej, Minolta, Sharp, and Toshiba. Xerox is a standard name for photocopiers and Xeroxing is a term that is identical with the word "photocopying". There is lot of potential for digital copiers but due to lack of awareness, the jobbers are not shifting to it. Also, there is lot of unpleasantness associated with after-sales service.